1992
DOI: 10.1159/000292717
|View full text |Cite
|
Sign up to set email alerts
|

Placental Villi-Decidua Interactions in Normal and Hypertensive Pregnancies: A Morphological Quantitative Study

Abstract: The decidual response to the implantation of the embryo is characterized by physical modifications to the uterine wall, with proliferation of the stromal cells which later change into decidual cells. We performed associated morphological and morphometrical studies to assess how the placental villi and decidua intersect, both in normal terminal pregnancy and in hypertensive patients in whom microenvironmental modifications induced by hypertension may cause significant alterations in mother-fetus relationships. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In addition, in diabetic pregnancies the evident increase of fibronectin in the umbilical vein wall [23] seems to reflect the already known increased syntheses of various extracellular matrix proteins, such as collagen IV, detect able in this disease [24], In conclusion, our studies show how the umbilical cord can actively respond to abnormal microenvironmental stimuli such as those occurring dur ing hypertension and diabetes, similarly to what was al ready observed in some of our other studies concerning an other embryonal appendage, the placenta [25,26], Furthermore, our present results clearly indicate how abnormal clinical conditions observed in the pregnant mother may represent a serious threat to fetal health with a possible feedback threat to the mother herself.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, in diabetic pregnancies the evident increase of fibronectin in the umbilical vein wall [23] seems to reflect the already known increased syntheses of various extracellular matrix proteins, such as collagen IV, detect able in this disease [24], In conclusion, our studies show how the umbilical cord can actively respond to abnormal microenvironmental stimuli such as those occurring dur ing hypertension and diabetes, similarly to what was al ready observed in some of our other studies concerning an other embryonal appendage, the placenta [25,26], Furthermore, our present results clearly indicate how abnormal clinical conditions observed in the pregnant mother may represent a serious threat to fetal health with a possible feedback threat to the mother herself.…”
Section: Discussionsupporting
confidence: 85%
“…In cases of PIH the physiological vascular changes are limited to some spiral arteries in the decidual segments with some remaining in the same state as spiral arteries in the non-pregnant uterus 20 . Biagini and co-workers 21 showed that in placentae of hypertensive women there is a higher number of chorionic villi-decidua interactions and a smaller surface area of a single interaction than in the placentae of normotensive women. Thus, the placental vascular interface between mother and fetus may be abnormal prior to the development of clinical PIH.…”
Section: Discussionmentioning
confidence: 99%